Establishment of a World Food Preservation Center: Concept, Need and Opportunity - Wilson , Charles L (Journal of Postharvest Technology, 2024)
The United Nations estimates that our  global population will increase by one  quarter and grow to 9.6 billion by 2050  (Anon, 2013). Most of this growth will  occur in urban areas and emerging  economies in Asia, Latin America, sub Saharan Africa. How we feed this  ballooning population will become one of  the most challenging problems of our time.  Awareness of this urgent issue is slow in  developing in the industrialized world  where food is generally abundant. Yet, the  primary responsibility for solving this  problem rests with developed countries.
Keywords: ballooning; population; Awareness; responsibility; agricultural